GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SDN WATUAGUNG KECAMATAN PRIGEN KABUPATEN PASURUAN - Badiatul Hikmah; Wachyudi Achmad (JIE (Journal of Islamic Education), 2017)
This study aimed to describe the style of leadership that is applied by the principle at SDN Watuagung in terms of the principal's role as an educator, manager, administrator, supervisor, innovator and motivator in improving teacher performance that includes four competencies are pedagogical, personality, professional, and social. This study used a qualitative approach to data collection methods, observation, interviews and documentation. Data analysis techniques using interactive analysis model Milles and Hubberman which includes four interrelated components, namely data collection, data reduction, data presentation, and conclusion. And for checking the validity of the data was use triangulation. The research findings of this study are: 1) the principal's leadership style in SDN Watuagung in improving teacher performance in terms of the role of the principal as an educator, manager, administrator, supervisor, innovator and motivator classified on charismatic leadership include impression management, emphasis on objectives ideological purpose that connects the group's mission to the values, ideals, and aspirations are rooted in the perceived with the subordinates, set an example in their own behavior that is followed by his subordinates, and motivation that are relevant to the vision and mission of the institution. Charismatic leadership that is applied by the principle at SDN Watuagung is motivated by the education background of the principle which is master of education management; 2) Improved performance of teachers conducted by the principal at SDN Watuagung includes increased pedagogical competence, personal competence, professional competence, and social competence.